Controlling amphipathic peptide adsorption by smart switchable germanium interfaces. Issue 8 (11th February 2022) - Baumgartner, Laura-Marleen; Erbe, Andreas; Boyle, Aimee L.; Rabe, Martin
Abstract : Control of reversible peptide adsorption and reorientation at the interface was achieved and studied on an electrically switchable germanium interface. Abstract : The in situ control of reversible protein adsorption to a surface is a critical step towards biofouling prevention and finds utilisation in bioanalytical applications. In this work, adsorption of peptides is controlled by employing the electrode potential induced, reversible change of germanium (100) surface termination between a hydrophobic, hydrogen terminated and a hydrophilic, hydroxyl terminated surface. This simple but effective 'smart' interface is used to direct adsorption of two peptides models, representing the naturally highly abundant structural motifs of amphipathic helices and coiled-coils. Their structural similarity coincides with their opposite overall charge and hence allows the examination of the influence of charge and hydrophobicity on adsorption. Polarized attenuated total reflection infrared (ATR-IR) spectroscopy at controlled electrode potential has been used to follow the adsorption process at physiological pH in deuterated buffer. The delicate balance of hydrophobic and electrostatic peptide/surface interactions leads to two different processes upon switching that are both observed in situ : reversible adsorption and reversible reorientation. Negatively charged peptide adsorption can be fully controlled by switching to the hydrophobic interface, while the same switch causes the positively charged, helical peptide to tilt down. This principle can be used for 'smart' adsorption control of a wider variety of proteins and peptides and hence find application, as e.g. a bioanalytical tool or functional biosensor.